Respuesta :

Answer:

The answer to your question is  y = -2x + 9

Step-by-step explanation:

A (9, 9)

B (-2, 13)

Process

1.- Find the slope

   m = [tex]\frac{y2 - y1}{x2 - x1}[/tex]

   [tex]m = \frac{13 + 9}{-2 - 9}[/tex]

  [tex]m = \frac{22}{-11}[/tex]

         m = - 2

2.- Find the line equation

         (y - y1) = m (x - x1)

          y + 9 = -2 (x - 9)               y + ? = [  ] ( x + [ ])

          y + 9 = - 2x + 18

          y = - 2x + 18 - 9

          y = -2x + 9

ACCESS MORE